The Effect of Final Irrigation Protocols on the Apical Sealing Ability of Epoxy Resin-based and Bioceramic-based Root Canal Sealers - Medhat, Anan; Ghoneim, Angie; Nabil Roshdy, Nehal (Open Access Macedonian Journal of Medical Sciences, 2022)
Aim: This study was designed to investigate the effect of different final irrigation protocols on the apical sealing ability of bioceramic and epoxy resin-based sealers. Materials and methods: Thirty human single-rooted mandibular premolars were instrumented using ProTaper Next rotary files. Teeth were randomly divided into three groups according to the final irrigation regimen; Group I: 5 ml 0.2% CNPs/3 min, Group II: 2.5 ml 0.2% CNPs/1.5 min followed by 2.5 ml 17% EDTA/1.5 min, and Group III: 5 ml 17% EDTA/3min. All groups were subdivided into two subgroups based on the obturation material; Subgroup A: gutta-percha/Sure-Seal Root BC Sealer and Subgroup B: gutta-percha/AH Plus. All canals were obturated using single cone obturation technique. The apical sealing ability was assessed using modified silver staining technique with ammoniacal silver nitrate tracer solution. Samples were sectioned longitudinally and examined using scanning electron microscope. Results: Sure-Seal Root BC sealer showed significantly lower nanoleakage compared to AH Plus (p < 0.001). No significant difference was recorded in the nanoleakage of Sure-Seal Root BC sealer among the three groups (p = 0.284), while AH Plus showed a significantly higher nanoleakage in the EDTA group (p = 0.002). The depth of silver nitrate penetration into the dentinal tubules was significantly higher in AH Plus subgroup with the three different irrigation protocols (p < 0.001). For both sealers, the highest penetration depth for silver nitrate tracer solution was recorded in the EDTA group (p < 0.001). Conclusions: The apical sealing ability of bioceramic sealers is better than that of epoxy resin-based sealers. The type of the final irrigating solution seems to affect the post-obturation seal of both AH Plus and Sure-Seal Root BC sealer. Keywords: Bioceramic, AH Plus, Chitosan nanoparticles, EDTA, Sealing ability.